2020
DOI: 10.1186/s12879-020-05499-1
|View full text |Cite
|
Sign up to set email alerts
|

Presence of urinary symptoms in bacteremic urinary tract infection: a retrospective cohort study of Escherichia coli bacteremia

Abstract: Background It is important to understand clinical features of bacteremic urinary tract infection (bUTI), because bUTI is a serious infection that requires prompt diagnosis and antibiotic therapy. Escherichia coli is the most common and important uropathogen. The objective of our study was to characterize the clinical presentation of E coli bUTI. Methods Retrospective cohort study of consecutive adult patients admitted for community acquired E. coli bacteremia from January 1, 2015 to December 31, 2016 was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Previous studies of IED have reported similar underlying medical conditions to those observed here, such as malignancy, diabetes mellitus, and chronic kidney disease [ 17–19 ]. Consistent with numerous reports, the urinary tract was the most commonly identified source of infection observed in 41.1% to 61.5% of patients [ 20–22 ]. The gastrointestinal tract was the second most common source, and it was most common in those with hospital-acquired IED.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies of IED have reported similar underlying medical conditions to those observed here, such as malignancy, diabetes mellitus, and chronic kidney disease [ 17–19 ]. Consistent with numerous reports, the urinary tract was the most commonly identified source of infection observed in 41.1% to 61.5% of patients [ 20–22 ]. The gastrointestinal tract was the second most common source, and it was most common in those with hospital-acquired IED.…”
Section: Discussionsupporting
confidence: 88%
“…The low effectiveness of UTI signs has already been described: Woodford et al reported the absence of UTI symptoms in half of an older population with UTI-related bacteremia in comparison to one-fifth of patients under 75 years of age [19]. Other studies confirm that only half of aged patients hospitalized for UTI have urinary symptoms [20][21][22][23][24]. Different hypotheses can be put forward to explain this low proportion.…”
Section: Discussionmentioning
confidence: 98%
“…Infections caused by Gram-negative bacilli (GNB) such as Enterobacterales are very common in emergency department (ED) settings. Many have urinary tract infections (UTIs) and some have complicated bloodstream infections (BSIs) other than UTIs [1]. Appropriate triage of patients with BSI in the ED is important because inappropriate use of antibiotics at the time of ED visit is associated with higher mortality [2,3].…”
Section: Introductionmentioning
confidence: 99%